the historical novel between the voice of heritage and identity Reading in the novel “Love at Night in the Presence of the One-eyed Antichrist” - بركات, محمد الأمين; بن عمار, هيثم (مجلة المخبر أبحاث في اللغة والأدب الجزائري, 2022)
Heritage is an essential component of identity, and identity expresses and transmits heritage. Nations are known for their heritage identities that are embodied by culture and civilization. Preserving heritage in its various forms, patterns and manifestations is a duty, responsibility and mission; It is an accumulated human asset that considers the nation’s wealth and its inexhaustible balance and the roots of its existence, and heritage is a source of knowledge and civilization that draws from it and builds upon it. Therefore, neglecting it was considered a stripping of identity and a denial of origins, and the continuity of generations through heritage in all its forms is a necessity to preserve its value and protect privacy. Cultural and civilizational, our heritage is a human civilization wealth that has enriched human knowledge through the ages of the nation's intellectual, literary and scientific history Keywords:  identity, heritage, novel, historical, glauji.